1995
DOI: 10.1177/028418519503600317
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization Transfer Contrast on Gradient Echo MR Imaging of the Temporomandibular Joint

Abstract: Thirty-nine temporomandibular joints (TMJ) from 20 patients with suspected internal derangements were imaged by a 1.5 T MR imager. The on-resonance binomial magnetization transfer contrast (MTC) pulse was applied to gradient echo images with a dual receiver coil (9 s/section). With the use of an opening device, a series of sequential images were obtained at increments of mouth opening and closing. The tissue signal intensities with (Ms) and without (Mo) MTC were measured and subjective image analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The signal intensity changes of masticatory muscles by clenching exercise and inflammatory process have previously been reported using T2-weighted FSE MR imaging [108], [109]. MTC images of the maxillofacial region show superior fluid conspicuity in the TMJ compared to conventional MR images [110]. In TMD patients, the MT ratios (MTRs; calculated as (Mo − Ms)/Mo, where Mo and Ms are the signal intensities of each muscle tissue before and after the saturation pulse is applied, respectively) of masseter muscles with pain symptoms caused by edematous changes are significantly lower than those of healthy muscles.…”
Section: Myositis and Muscle Edema/contracture-related Myofascial Paimentioning
confidence: 79%
“…The signal intensity changes of masticatory muscles by clenching exercise and inflammatory process have previously been reported using T2-weighted FSE MR imaging [108], [109]. MTC images of the maxillofacial region show superior fluid conspicuity in the TMJ compared to conventional MR images [110]. In TMD patients, the MT ratios (MTRs; calculated as (Mo − Ms)/Mo, where Mo and Ms are the signal intensities of each muscle tissue before and after the saturation pulse is applied, respectively) of masseter muscles with pain symptoms caused by edematous changes are significantly lower than those of healthy muscles.…”
Section: Myositis and Muscle Edema/contracture-related Myofascial Paimentioning
confidence: 79%
“…MT has been found to cause maximal suppression of signal in normal muscle and hyaline cartilage, moderate suppression of signal in normal brain and liver, and very minimal or no suppression of signal in fluid, blood and fat [4,11]. Thus most clinical applications that have been identified for MT imaging are in the brain and, to a lesser extent, the musculoskeletal system [2,4,7,8]. Conventional MR pulse sequences can demonstrate pathology in dermatomyositis, hemophilia, trauma and nerve tumors [10, 12,13,14]; we have demonstrated that MT can consistently provide contrast differences between the normal and pathological tissues in these disorders in children.…”
Section: Discussionmentioning
confidence: 99%
“…MT has been noted to decrease the signal from some normal tissues [4]. It has already been successfully utilized in aduits, particularly in the brain for MR angiography studies [3,4], and for imaging of hyaline cartilage [4,7] and muscle tumors [8]. The objective of this article is to demonstrate MT contrast in images of the musculoskeletal system in children.…”
Section: Introductionmentioning
confidence: 99%